Ответ:
ниже
Пошаговое объяснение:
1. а*(а+b)-a*(a-b)/(a-b)*(a+b) * a+b/a
а^2+аb-a^2+ab/a-b * 1/2 (сокращаем а^2; приводим подобные числа)
2аb/a-b*1/а
2b/a-b*1/а
ответ : 2b/a-b*1/а
2. 6
+ 0,5 * 2
- 15![\sqrt{2} \sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
6
+
-15![\sqrt{2} \sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
-8![\sqrt{2} \sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
ответ : -8![\sqrt{2} \sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
3. х^2-x-4x+4=0
x*(x-1)-4(x-1)=0
(x-1)*(x-4)=0
x=1 x=4
ответ : x=1 x=4